Accuracy of screw placement and radiation dose in navigated dorsal instrumentation of the cervical spine: a prospective cohort study. Issue 2 (23rd December 2013) - Kraus, Michael; von dem Berge, Stephanie; Perl, Mario; Krischak, Gert; Weckbach, Sebastian
Abstract Background Dorsal cervical spinal fusion is a challenging procedure in fracture fixation. There is limited information in the literature about computer navigation using lateral mass screws in cases of spinal trauma. Methods Retrospective analysis of a prospective database covering an 8 year period. All patients who received a dorsal spinal fusion due to a fracture of the cervical spine were included. Outcome parameters were screw accuracy, duration of surgery, the radiation emitted and intra‐/postoperative complications. Results Sixteen patients, who received 67 screws (44 navigated vs 23 conventionally inserted screws) were included. Three‐dimensional (3D)‐based computer navigation prolonged the duration of surgery but helped to reduce the radiation emitted and led to significantly increased accuracy of screw positioning. Conclusion Computer navigation can increase the accuracy of lateral mass screws in spinal trauma. It prolongs the surgical procedure but reduces the emission of radiation significantly. Copyright © 2013 John Wiley & Sons, Ltd.